Big business stability and economic growth: Is what's good for General Motors good for America?☆ - FOGEL, K; MORCK, R; YEUNG, B (Journal of Financial Economics, 2008)
What is good for a country may not be good for its big businesses, at least recently. More turnover in top businesses correlates with faster per capita gross domestic product, productivity, and capital growth; supporting Schumpeter's [1942. Capitalism, Socialism and Democracy, third ed., Harper & Bros., New York, NY] theory of “creative destruction”—innovative firms blooming as stagnant ones wither. These correlations are greater in more developed economies, supporting Aghion and Howitt's [1992. A model of growth through creative destruction. Econometrica 60, 323–351] thesis that creative destruction matters more to economies nearer the technological frontier. More big business turnover also correlates with smaller government, common law, less bank-dependence, stronger shareholder rights, and greater openness.